Microbial antibiotic resistance genes across an anthropogenic gradient in a Canadian High Arctic watershed - Provencher, Juliette; George, Paul B. L.; Thaler, Mary; Vincent, Warwick F.; Duchaine, Caroline; Culley, Alexander; Girard, Catherine (Sustainable Microbiology, 2025)
Antibiotic resistance is one of the biggest challenges to public health. While the disco v ery of antibiotics has decreased pathogen-caused mort alit y, the o v er use of these dr ugs has resulted in the increased transfer and e v olution of antibiotic resistance genes (AR Gs) in bacteria. AR Gs naturally occur in wild bacterial communities, but are also found in increased concentrations in environments contaminated by wastewater effluent. Although such ARGs are relatively well described in temperate environments, little is known about the distribution and dissemination of these genes in the Arctic. We characterized the ARGs in microbial communities from aerosols, lakes and microbial mats around a remote Arctic hamlet using metagenomic approaches. Specific objectives were to (i) compare ARGs across habitats, (ii) to characterize ARG populations along a continuum of anthropogenically influenced environments, and (iii) to identify ARGs of viral origin. We identified ARGs in all habitats throughout the watershed, and found that microbial mats in the most impacted area had the highest diversity of ARGs relative to uncontaminated sites, which may be a remnant signal of w aste w ater effluent inputs in the area during the 20th century. Although we identified ARGs predominantly in bacterial genomes, our data suggests that mimiviruses may also harbor ARGs.